MANAJEMEN KEPALA SEKOLAH DALAM IMPLEMENTASI SISTEM INFORMASI PENDIDIKAN DI ERA DIGITAL - Mukhlizar Mukhlizar (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2026)
Digital transformation has fundamentally reshaped the paradigm of educational management, making the implementation of Educational Information Systems (EIS) a strategic necessity for enhancing the effectiveness of school governance. The successful implementation of these systems is largely determined by the principal's managerial capacity to integrate core management functions with digital leadership competencies. This study aims to analyze the role of school principals in managing Educational Information Systems, identify implementation strategies along with their opportunities and challenges, and propose a digital-based school management model to improve the effectiveness of Educational Information Systems in the digital era. This study employed a qualitative approach using a library research design. Data were collected from scholarly books, national and international journal articles, conference proceedings, and relevant policy documents. The data were analyzed through content analysis involving data reduction, data organization, interpretation, and conclusion drawing. The findings reveal that the successful implementation of Educational Information Systems depends on the effective execution of managerial functions, including planning, organizing, actuating, and controlling, supported by digital leadership, human resource capacity development, data-driven governance, and an organizational culture that embraces digital transformation. Although challenges such as limited digital competencies, inadequate technological infrastructure, data security concerns, and resistance to organizational change remain significant, the implementation of Educational Information Systems offers substantial opportunities to improve administrative efficiency, transparency, accountability, and evidence-based decision-making. This study proposes a digital-based school principal management model as a conceptual framework for strengthening educational governance and fostering sustainable school quality improvement in the era of digital transformation.